Inhibition of Human Breast Carcinoma Cell Proliferation by Ascorbate and Copper - González, Michael J.; Mora, Edna M.; Miranda-Massari, Jorge R.; Matta, Jaime; Riordan, Hugh D.; Riordan, Neil H. (Puerto Rico Health Sciences Journal, 2013)
see manuscript